Namibia : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
Namibia's government has launched a major three-year fiscal initiative in 2011 aimed at increasing growth and employment. Public debt is rising rapidly, from a low base. The authorities intend to unwind the fiscal expansion in 2014. Fiscal consolidation would help keep public debt to a manageable level, support the economy's external position, and provide room to maneuver if further shocks arise, including a potential fall in revenues from the Southern African Customs Union. The authorities reaffirmed their intention to support the exchange rate peg against the South African rand.